Leishmania infantum amastin protein incorporated in distinct adjuvant systems induces protection against visceral leishmaniasis. (May 2020) - Ribeiro, Patrícia A.F.; Vale, Danniele L.; Dias, Daniel S.; Lage, Daniela P.; Mendonça, Débora V.C.; Ramos, Fernanda F.; Carvalho, Lívia M.; Carvalho, Ana Maria R.S.; Steiner, Bethina T.; Roque, Marjorie C.; Oliveira-da-Silva, João A.; Oliveira, Jamil S.; et al.
Graphical abstract: Highlights: L. infantum amastin protein was tested as a vaccine against VL. Distinct immune adjuvants were used together with the recombinant protein. The amastin/liposome composition was the most immunogenic in the vaccinated animals. It induced higher protective efficacy against L. infantum infection. The amastin protein was immunogenic in human PBMCs with a Th1-type profile has been found. Abstract: The control measures against visceral leishmaniasis (VL) include a precise diagnosis of disease, the treatment of human cases, and reservoir and vector controls. However, these are insufficient to avoid the spread of the disease in specific countries worldwide. As a consequence, prophylactic vaccination could be interesting, although no effective candidate against human disease is available. In the present study, the Leishmania infantum amastin protein was evaluated regarding its immunogenicity and protective efficacy against experimental VL. BALB/c mice immunized with subcutaneous injections of the recombinant protein with or without liposome/saponin (Lip/Sap) as an adjuvant. After immunization, half of the animals per group were euthanized and immunological evaluations were performed, while the others were challenged with L. infantum promastigotes. Forty-five days after infection, the animals were euthanized and parasitological and immunological evaluations were performed. Results showed the development of a Th1-type immune response in rAmastin-Lip and rAmastin-Sap/vaccinated mice, before and after infection, which was based on the production of protein and parasite-specific IFN-γ, IL-12, GM-CSF, and nitrite, as well as the IgG2a isotype antibody. CD4 + T cells were mainly responsible for IFN-γ production in vaccinated mice, which also presented significant reductions in parasitism in their liver, spleen, draining lymph nodes, and bone marrow. In addition, PBMC cultures of treated VL patients and healthy subjects stimulated with rAmastin showed lymphoproliferation and higher IFN-γ production. In conclusion, the present study shows the first case of an L. infantum amastin protein associated with distinct delivery systems inducing protection against L. infantum infection and demonstrates an immunogenic effect of this protein in human cells.